The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.31895/hcptbn.16.1-2.5
|View full text |Cite
|
Sign up to set email alerts
|

The assesement of bioactive potential and sensory acceptability of coffee and its byproducts- cascara and silverskin

Abstract: Through the decades, coffee has been representing one of the most consumed beverages worldwide and consequently, during the coffee cherry processing, significant amount of coffee byproducts is generating, thus ending as an agro- industrial waste. Besides macro and micronutrient content, coffee cascara and coffee silverskin are coffee by-products which can have valuable bioactive potential. For that purpose, ethanol extracts and water infusions (beverages) of green coffee, roasted coffee, coffee cascara and cof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
(27 reference statements)
1
2
0
Order By: Relevance
“…Furthermore, we observed the absence of 3,5-dicaffeoylquinic acid in samples 1S, 2S, and 1C and the absence of 4,5-dicaffeoylquinic acid in samples 1S and 2C. Mandura et al (2021) [6] also reported similar phenomena. Moreover, the same authors found that the caffeine content of cascara reached 9.20 ± 0.50 mg•g −1 and silverskin 5.30 ± 0.2 mg•g −1 .…”
Section: Chlorogenic Acids (Cgas) and Caffeinesupporting
confidence: 76%
See 2 more Smart Citations
“…Furthermore, we observed the absence of 3,5-dicaffeoylquinic acid in samples 1S, 2S, and 1C and the absence of 4,5-dicaffeoylquinic acid in samples 1S and 2C. Mandura et al (2021) [6] also reported similar phenomena. Moreover, the same authors found that the caffeine content of cascara reached 9.20 ± 0.50 mg•g −1 and silverskin 5.30 ± 0.2 mg•g −1 .…”
Section: Chlorogenic Acids (Cgas) and Caffeinesupporting
confidence: 76%
“…The main factors affecting the caffeine content of cascara include the fermentation process, botanical origin, variety, post-harvest processing, time, and method of extract preparation [6,46,62]. Comparable results of caffeine content in silverskin reaching 6.50 ± 0.60 mg•g −1 were published by Cantele et al [58].…”
Section: Chlorogenic Acids (Cgas) and Caffeinementioning
confidence: 84%
See 1 more Smart Citation